Peran Brand Familiarity Dalam Memediasi Brand Authenticity Dan Brand Engagement Pada Loyalitas Wisatawan Di Tawangmangu - Sabiila Indra Prameswari; Imronudin Imronudin; Liana Mangifera (JURNAL LENTERA BISNIS, 2023)
This study aims to develop and explore a conceptual framework to explain the relationship between destination brand authenticity, destination brand engagement, destination brand familiarity, and tourist loyalty. With a total of 120 respondents who filled out questionnaires via the Google form. The sampling technique used purposive sampling technique. For data analysis using Structural Equation Model (SEM) analysis with Smart Partial Least Square (PLS). In this study, the sample used was tourists who are domiciled in Solo Raya, with a population of tourists who have visited Tawangmangu in the past year. The results of the study show that destination brand familiarity mediates the relationship between destination brand authenticity and brand involvement on tourist loyalty. So it can be concluded that the results of this study can help destination marketing organizations realize the important role of destination brand familiarity and improve brand performance.Keywords: Familiarity, Authenticity, Engagement, Tourist Loyalty